Pre-diagnostic Circulating Parathyroid Hormone Concentration and Colorectal Cancer in the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort - Fedirko, Veronika (2011)
BACKGROUND: Parathyroid hormone (PTH) has been proposed to play a promoting role in carcinogenesis. However, no epidemiologic studies have yet directly investigated its role in colorectal cancer (CRC). METHODS: A case-control study nested within the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort was conducted with 1,214 incident, sporadic CRC cases matched to 1,214 controls. Circulating pre-diagnostic PTH and 25-hydroxy vitamin D [25(OH)D] concentrations were measured by enzyme-linked immunosorbent assays. Detailed dietary and lifestyle questionnaire data were collected at baseline. Multivariable conditional logistic regression was used to estimate the incidence rate ratio (RR) with 95% confidence intervals (95%CI) for the association between circulating PTH and CRC risk. RESULTS: In multivariate analyses (including adjustment for 25(OH)D concentration) with a priori defined cut-points, high levels of serum PTH (≥65ng/L) compared to medium PTH levels of 30–65 ng/L were associated with increased CRC risk (RR=1.41, 95%CI: 1.03-1.93). In analyses by sex, the CRC risk was 1.77 (95%CI: 1.14-2.75) and 1.15 (95%CI: 0.73-1.84) in men and women, respectively (P(heterogeneity)=0.01). In sub-group analyses by anatomical sub-site, the risk for colon cancer was RR=1.56, 95%CI:1.03-2.34, and for rectal cancer RR=1.20, 95%CI:0.72-2.01 (P(heterogeneity)=0.21). Effect modification by various risk factors was examined. CONCLUSIONS: The results of this study suggest that high serum PTH levels may be associated with incident, sporadic CRC in Western European populations, and in particular among men. IMPACT: To our knowledge, this is the first study on PTH and CRC. The role of PTH in carcinogenesis needs to be further investigated.